Identifying the resonance curve of a system subjected to linear and quadratic parametric excitations (case without damping) - Dinh, Nguyen Van; Chi, Tran Kim (Vietnam Journal of Mechanics, 1999)
Continuing our study in [3], in the present paper we examine the system without damping h = 0. In this particular case, the original equations and the associated ones are very simple and can easily be solved.